Fossil Bovidae (Mammalia: Artiodactyla) from southern Africa: Biochronology and palaeoenvironments - Raphaël Hanon; Christine Steininger (Quaternary Environments and Humans)
Bovids are usually the most common large mammal family encountered in archaeological accumulations from African sites. However, despite their dominant status in bone assemblages, there are proportionally very few taxonomic studies of the southern African material. Here, we provide the first updated overview of the Southern African Bovidae fossil record from the Miocene to the Holocene. We used the bovid faunal list from 95 deposits comprising 65 species to provide an updated biochronology based on bovid assemblages. We define six bovid units (“Standard Bovid Units”) that will help to estimate the geological age of future deposits. Interestingly, the refined biochronology based on bovid assemblages does not fundamentally change from previous large mammal biochronological systems provided for the Cenozoic of Southern Africa. This strengthens the fact that bovids are a powerful proxy for biochronology that are still relevant today and incredibly stable over time. Unsurprisingly, the palaeoecological analysis based on bovid assemblages confirms the global aridification of the African continent throughout the Quaternary. Moreover, we identified an important gap in the fossil record between 5.1 and 2.6 Ma, highlighting a need to pursue effort on fieldwork and to provide detailed taxonomic analysis of bovid bone assemblages systematically.